First reported case of fetal maceration in a wildlife Iberian red deer - Amanda García del Rincón-Garoz; Concepción Azorit (Journal of Applied Animal Research)
In this paper, we describe for the first time a finding of fetal maceration in a wild Iberian hind (Cervus elaphus hispanicus, Erxleben, 1777). Fetal maceration seems to occur in fetuses that have died and have not been expelled due to insufficient dilation of the cervix, but which allows the penetration and ascent of germs through the birth canal. It can occur at any stage of gestation, although it is more common in mid to late gestation. In our case, the stage of development and skeleton ossification and the degree of eruption of the premolar teeth of the mandible allow us to infer that the death of the fetus and the process of maceration occurred from the end of gestation. This discovery occurred during the butchering of a female hunted as part of the management programme to reduce the abundance of the population in Quintos de Mora, Spain. Although the female was in good body condition, she was selected because she had no calf and had an aged appearance. We describe the case in detail and draw attention to the interest of recording the rates of pregnancy losses and abortions in studies of fitness and population dynamics in wildlife.